PENGARUH BEBAN PAJAK TANGGUHAN, TAX PLANNING, DAN TAX AVOIDANCE TERHADAP MANAJEMEN LABA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2021 – 2023 - Saputro, Isman Ardi; Mulyaningtyas, Alvy (Politeknik Negeri Ambon, 2025)
Introduction: Earnings management has become a phenomenon of interest because it provides insight into managers’ behavior in reporting business activities over a specific period and the potential for particular motivations to manipulate reported financial data. This study aims to analyze the effect of deferred tax burden, tax planning, and tax avoidance on earnings management in food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2023.Methods: This study employs quantitative methods, using secondary data —specifically, company financial reports. The population in this study is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. This study employs quantitative methods, utilizing secondary data, specifically company financial reports obtained from the IDX website and through documentation techniques. The population in this study is food and beverage sub-sector companies listed on the IDX from 2021 to 2023. A sample of 19 companies was obtained using a purposive sampling method.The analytical method in this study is descriptive analysis.Results: The study’s F-test revealed that the deferred tax expense, tax planning, and tax avoidance variables collectively had a significant impact on earnings management. Keywords: Deferred Tax Burden, Tax Planning, Tax Avoidance, Earnings Management